Herders are networking in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Animal breeding, pasture development and foraging in developing countries tended to be overlooked by agricultural researchers for many years. Over the last decade, however, the importance of pasturing has been acknowledged and initial steps have...